Students’ Responses to Teacher’s Reinforcement: A Discourse Analysis - Pemilda Alphania Meizy; Bambang Suharjito; Annur Rofiq (Journal of English Education and Teaching, 2022)
Reinforcement is one of the important aspects in increasing students' motivation, to be more serious, and more focused during the teaching-learning process. This research is intended to know the kinds of reinforcement used by the teacher, how students respond to it, and how was their feeling about it. The design of this research is Discourse Analysis that focuses on the semiotic area. This research was conducted at one of the state junior high schools in East Java, Indonesia. The participant was chosen by using purposive sampling method and class 7F students were selected as the research participants. In conducting the research, the researcher did classroom observation, took video recording, and did an interview with the students to know exactly the meaning of students' responses. The finding showed that the teacher used verbal and non-verbal reinforcement. Mostly, the teacher praised the students for what they have done and students mostly showed their response using facial expression and sometimes using body gesture. Regarding their feeling, they said that reinforcement from the teacher makes them feel appreciated, motivated and happy during the teaching-learning process, which means that the role of reinforcement is very important.